2005
DOI: 10.1021/ma048154c
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Copolymer Composition in High Conversion Copolymerization of Acrylonitrile and Methyl Acrylate Assessed by in Situ 13C NMR Measurements of Individual Monomer Reaction Rates

Abstract: The copolymerization of acrylonitrile with methyl acrylate initiated by azobis(isobutyronitrile) in dimethyl sulfoxide at 60 °C has been investigated to high conversion using in situ 13 C NMR spectroscopy. The focus has been on the relative rates of individual monomer consumption as a function of time up to as high a conversion as experimentally feasible. It has been found that the relative rates of monomer consumption, i.e., the instantaneous copolymer composition, cannot be described by the low conversion va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This clearly rules out the formation of random copolymers. Since the monomer feed composition strongly changes with conversion, the reactivity ratios will depend upon the conversion and therefore, would not be meaningful in commenting about the copolymer structure . The huge reactivity difference between AN and NAGA hint about the formation of block/gradient‐type copolymers or a grafted copolymer structure with PAN backbone with grafts of NAGA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly rules out the formation of random copolymers. Since the monomer feed composition strongly changes with conversion, the reactivity ratios will depend upon the conversion and therefore, would not be meaningful in commenting about the copolymer structure . The huge reactivity difference between AN and NAGA hint about the formation of block/gradient‐type copolymers or a grafted copolymer structure with PAN backbone with grafts of NAGA.…”
Section: Resultsmentioning
confidence: 99%
“…The graft structure is possible by transfer reactions generating radicals on PAN backbone followed by NAGA polymerization. The formation of block copolymers as well as a grafted copolymer structure by simultaneous polymerization of two comonomers in one‐pot is rare, but already known in the literature for other comonomer systems . The formation of a blend of two homopolymers during polymerization or presence of homo PAN in copolymers is ruled out based on the combination of following facts: (a) monomodal GPC curves and (b) PAN homopolymer is not soluble in water at any temperature, whereas the polymer showed thermoresponsive behavior (described below) without traces of any insoluble part in the solution above cloud point.…”
Section: Resultsmentioning
confidence: 99%
“…However, if the viscosity is high enough, it is possible that the propagation step will also become diffusion controlled instead of chemically controlled. Indeed, it has been reported that the propagation rate constant for acrylate polymerization, which have rate constants about four orders of magnitude greater than traditional methacrylates, can indeed be reduced at moderately high viscosities,15 whereas for similarly structured methacrylates, the viscosity of the medium must be extremely high to result in diffusion‐controlled propagation rate constants. Consequently, the rate constants for tributylmethylammonium methacrylate and butyl methacrylate at 25 and 80 °C are comparable, and in fact the rate constants for tributylmethylammonium methacrylate when consideration is given to the differences in the double bond concentration are measurably larger than for butyl methacrylate.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of ylides are very dependent on the identity of the heteroatoms. 2 A literature survey has shown copolymerizations of methyl acrylate (MA) with styrene, 3 5-ethyl-2-vinyl pyridine, 4 and acrylonitrile 5 and copolymerizations of 4-vinyl pyridine (4-VP) with methyl methacrylate 6 and styrene 7 with imidazolium-p-chlorophenacylide, 3 azobisisobutyronitrile, 4,5 and b-picolinium-p-chlorophenacylide 6,7 used as radical initiators.…”
Section: Copolymerizationmentioning
confidence: 99%